PERSEPSI PENGUNJUNG TERHADAP PENGEMBANGAN EKOWISATA DI KEBUN RAYA LIWA - haqfini bina lalika; susni herwanti; indra gumay febryano; gunardi djoko winarno (Forestry Study Program University Of Mataram, 2020)
Visitors' perception can be used as a source to develop ecotourism object. The purpose of this research was to explain visitors' perception towards the development of ecotourism object in Liwa Botanical Garden. The data taken through closed-interview, observation and literature study. The data collected was analyzed by one score one indicator. The result of the research showed that the attraction object in Liwa Botanical Garden was quite satisfying: infrastructures, facilities, and services were categorized as satisfying: however the acomodation was less satisfying. The additional and restoration of plant collection, food stalls, parking lot, guard post, gate, the color of footpath, children play zone, and camping ground need to be fixed.